1992
DOI: 10.1037/0735-7044.106.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amygdala lesions on reflex facilitation and conditioned response acquisition during nictitating membrane response conditioning in rabbit.

Abstract: The present study demonstrated that large lesions of the amygdala disrupt the maintenance of reflex facilitation of the unconditioned nictitating membrane (NM) response and slow the acquisition of conditioned NM responses in rabbit. Before behavioral training, the central nucleus of the amygdala and adjacent areas were lesioned electrolytically. In the 1st experiment, the lesioned animals exhibited no reflex facilitation of the unconditioned NM response at conditioned stimulus (CS)-unconditioned stimulus (US) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 37 publications
7
105
2
Order By: Relevance
“…In addition to the aforementioned behavioral observations of Vandercar and Schneiderman (1967;see also Brandon, Betts, &Wagner, 1994, and showing differential variation as a function of the CS-US interval, there is substantial literature attesting to the differential speed ofacquisition ofthe two measures (see review by Lennartz & Weinberger, 1992; but see also Kehoe &Macrae, 1994, andWeinberger, 1994), and the report of Betts, Brandon, and Wagner (1996) showing that shift of the US from one eye to the other spares blocking ofconditioned fear but not blocking of conditioned eyeblink. These behavioral observations are supported by neurobiological investigations that suggest that the locus of neural convergence essential for eyeblink conditioning is different from that for fear conditioning (e.g., Thompson, 1986): Instructive is the fact that cerebellar damage that prevents eyeblink conditioning does not prevent fear conditioning (Thompson et a!., 1986), whereas amygdala lesions that interfere with fear conditioning do not preclude eyeblink conditioning (e.g., Weisz, Harden, & Xiang, 1992). The body of evidence, including the differential effects of backward conditioning reported by Tait and Saladin (1986) and confirmed in Experiments 1 and 2, is consistent with those treatments of Pavlovian conditioning (e.g., Konorski, 1967;Wagner & Brandon, 1989;Weinberger, 1982) that suppose that different associations underlie specific conditioned reflexes, such as the eyeblink, versus more generally influential conditioned emotional responses, such as conditioned fear, which may be concurrently acquired.…”
Section: Resultsmentioning
confidence: 54%
“…In addition to the aforementioned behavioral observations of Vandercar and Schneiderman (1967;see also Brandon, Betts, &Wagner, 1994, and showing differential variation as a function of the CS-US interval, there is substantial literature attesting to the differential speed ofacquisition ofthe two measures (see review by Lennartz & Weinberger, 1992; but see also Kehoe &Macrae, 1994, andWeinberger, 1994), and the report of Betts, Brandon, and Wagner (1996) showing that shift of the US from one eye to the other spares blocking ofconditioned fear but not blocking of conditioned eyeblink. These behavioral observations are supported by neurobiological investigations that suggest that the locus of neural convergence essential for eyeblink conditioning is different from that for fear conditioning (e.g., Thompson, 1986): Instructive is the fact that cerebellar damage that prevents eyeblink conditioning does not prevent fear conditioning (Thompson et a!., 1986), whereas amygdala lesions that interfere with fear conditioning do not preclude eyeblink conditioning (e.g., Weisz, Harden, & Xiang, 1992). The body of evidence, including the differential effects of backward conditioning reported by Tait and Saladin (1986) and confirmed in Experiments 1 and 2, is consistent with those treatments of Pavlovian conditioning (e.g., Konorski, 1967;Wagner & Brandon, 1989;Weinberger, 1982) that suppose that different associations underlie specific conditioned reflexes, such as the eyeblink, versus more generally influential conditioned emotional responses, such as conditioned fear, which may be concurrently acquired.…”
Section: Resultsmentioning
confidence: 54%
“…The present finding that afferent limb emotional conditioning processes are essential for the cingulothalamic changes that support instrumental avoidance learning provides the first putative identification of separate neuroanatomical substrates of the two processes, as well as anatomical and physiological links between them. This suggested division of function is also supported by the demonstrations that (1) acquisition and maintained performance of aversively motivated Pavlovian conditioned responses (CRs) require an intact amygdala (Weisz et al, 1992;Lee et al, 1996;; (2) acquisition and performance of at least one variety of aversively motivated Pavlovian CR, the eye blink CR, do not require intact cingulothalamic circuitry ; and (3) the contribution of the amygdala to aversively motivated instrumental learned responses diminishes as experience accumulates in a given task (Parent et al, 1992;Roozendaal et al, 1993;Poremba and Gabriel, 1995).…”
Section: Implications For F Unctional Organization Of the Learning-rementioning
confidence: 74%
“…Studies using rabbits have revealed that animals exhibit conditioned bradycardia (decreased heart rate) responses during the early phase of eyeblink conditioning (Yehle, 1968; Lavond et al, 1984). Amygdala lesions have been shown to abolish conditioned bradycardia and reflex facilitation of nictitating membrane responses and retard the learning of eyeblink CR (Weisz et al, 1992;Chachich and Powell, 1998). Conversely, electrical stimulation of amygdalar central nucleus has been found to decrease heart rate and increase nictitating membrane response amplitudes (Whalen and Kapp, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that nonspecific emotional responses facilitate the subsequent acqui-sition of specific motor responses (Lennartz and Weinberger, 1992;Mintz and Wang-Ninio, 2001). In support, lesions to the amygdala, which abolish fear conditioning (Blanchard and Blanchard, 1972;Kim et al, 1993;LeDoux, 2000), reduce the CSinduced reflex facilitation of eyeblink UR and retard the acquisition of eyeblink CR in rabbits (Weisz et al, 1992). Additionally, rats that first underwent fear conditioning subsequently displayed facilitated motor conditioning (Neufeld and Mintz, 2001).…”
Section: Introductionmentioning
confidence: 99%